2015
DOI: 10.1111/jcpe.12451
|View full text |Cite
|
Sign up to set email alerts
|

Acute‐phase response following full‐mouth versus quadrant non‐surgical periodontal treatment: A randomized clinical trial

Abstract: FM-SRP triggers a moderate acute-phase response of 24 h duration compared to Q-SRP. Further research is needed to assess the eventual impact of such findings on the risk of vascular events is advocated. (ClinicalTrials.gov NCT01857804).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
78
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(91 citation statements)
references
References 37 publications
11
78
1
1
Order By: Relevance
“…Comparison of FMD and Q-SRP revealed that FMD was moderately better than Q-SRP in reducing probing depth and increasing clinical attachment level (13). Therefore, we used FMD and FM-SRP as the treatment of choice to restrict the cumulative effect of bacteremia and avoid repeated acute inflammation during treatment (16,17). As a result, significant improvements were observed in all periodontal parameters throughout the study period in both groups.…”
Section: Discussionmentioning
confidence: 99%
“…Comparison of FMD and Q-SRP revealed that FMD was moderately better than Q-SRP in reducing probing depth and increasing clinical attachment level (13). Therefore, we used FMD and FM-SRP as the treatment of choice to restrict the cumulative effect of bacteremia and avoid repeated acute inflammation during treatment (16,17). As a result, significant improvements were observed in all periodontal parameters throughout the study period in both groups.…”
Section: Discussionmentioning
confidence: 99%
“…Although SRP improves systemic inflammation in the long term, intense non‐surgical periodontal therapy including FM‐SRP acts as a potent inflammatory stimulus immediately after treatment, and induces an acute inflammatory response . Recently, Graziani et al reported that FM‐SRP results in a strong systemic acute‐phase response that includes CRP and IL‐6, after 24 hours in patients with periodontitis. It is thus a concern that the marked systemic spread of inflammatory mediators from periodontal pockets and tissues following FM‐SRP might cause transient hypercytokinemia.…”
Section: Introductionmentioning
confidence: 99%
“…Most previous studies in this field have mainly focused on the clinical and microbiological effects of FM‐SRP; knowledge of the contribution of FM‐SRP to the systemic biological response is limited. In addition, little information is available regarding the systemic acute‐phase response including fever and the production of inflammatory mediators after FM‐SRP . Furthermore, as far as we are aware, no study has concurrently evaluated changes in serum and gingival crevicular fluid inflammatory markers.…”
Section: Introductionmentioning
confidence: 99%
“…Recent data suggested that NSPT performed fully within 24 hours may induce greater disturbance of systemic inflammation when compared with quadrant scaling . To overcome this issue, different modifications to the original FMD protocol have been proposed.…”
Section: Introductionmentioning
confidence: 99%